Sexual dysfunction among youth: an overlooked sexual health concern - Caroline Moreau; Anna E Kågesten; Robert Wm Blum (BMC, 2016)
Abstract Background There is growing recognition that youth sexual health entails a broad range of physical, emotional and psychosocial responses to sexual interactions, yet little is known about sexual dysfunctions and well being in youth populations. This study explored sexual dysfunctions among youth and its associations with other domains of sexual health. Sexual dysfunctions were defined as: problems related to orgasm, pain during intercourse, lack of sexual desire or sexual pleasure. Methods Data were drawn from the 2010 French national sexual and reproductive health survey comprising a random sample of 2309 respondents aged 15-24 years. The current analysis included 842 females and 642 males who had sexual intercourse in the last 12 months. Chi square tests were used to test for differences in sexual dysfunctions by sex and explore associations with other domains of sexual health. Results Half of females (48%) reported at least one sexual dysfunction versus 23% of males. However, over half (57%) of youth reporting at least one dysfunction did not consider this to hinder their sexuality. Altogether, 31% of females cited at least one sexual dysfunction hindering their sexuality-more than three times the 9% of males. Sexual dysfunction was strongly and inversely related to sexual satisfaction for both males and females and additionally to a recent diagnosis of STI or unintended pregnancy for females. Sexual dysfunctions hindering sexuality were also correlated with a history of unintended pregnancy among males. Conclusion While most youth in France enjoy a satisfying sexual life, sexual dysfunction is common, especially among females. Public health programs and clinicians should screen for and address sexual dysfunction, which substantially reduce youth sexual wellbeing.